Pendidikan Dan Pelatihan Menjaga Kesehatan Rongga Mulut Dan Umum Pada Lansia Di Yayasan Uswatun Hasanah Pusaka 67, Cengkareng, Jakarta Barat - Ariesanti, Yessy; Melanie S. Djamil; Yuniar Zen; Mikha Sundjojo; Rasad, Irvan; Jonathan Rafel Ohary (JUARA: Jurnal Wahana Abdimas Sejahtera, 2024)
Elderly’s population continues to rise globally, including Indonesia. Based on Government Regulation of Republic of Indonesia Number 43/2004, elderly is stated as someone whose age is above 60 years. Elderly population has experienced a decline in health because their body functions decreased due to increase of age. Aging process can cause a decrease in organ function as well as various physical changes, including changes in the oral cavity. Elderly can increase physical activity to make them fit and healthy. Dental problems that often occur in Indonesia on elderly are caries with 96.8% in the age range from 55-64 years, and 95.0% in ages >65 years. Problems with periodontitis at the age of 55-64 years with 75.9% and ages > 65 years with 66.0%. If this is not treated, it can lead to tooth loss which will interfere the function and activities of the oral cavity and have an impact on the quality of life. In Indonesia, herbs have been widely used for maintenance and health care which are indicated to be useful for treatment including dental issues, which is lemongrass and betel leaf. This community service has the goal to educate, train the elderly to maintain dental and general health by doing physical activities together to maintain and improve their health status. Implementation method is carried out by conducting survey, data collection and offline socialization. After the activities were carried out, the elderly understood how to maintain oral health using herbs and body’s health.